A Transient Conducted EM Disturbances Source Modeling Method for Electromagnetic Launch System Based on the Cascaded Multi-Port Circuit Model - Bailin Mou; Qi-Feng Liu; Zhenya Chen; Xiaowen Wu; Yongming Li; Chen Huang; Huai-Qing Zhang (IEEE Access)
Electromagnetic launch (EML) systems with energy storage units in transient operating states are gradually being applied in modern ships, satellite launches, etc., power switching devices with higher voltage and switching frequency, Additionally, innovative topologies are being developed to enhance the electromagnetic performance of the EML systems. This inevitably leads to significant EMI issues. Therefore, this paper proposes a transient conducted EMI source modeling method for EML systems based on a multi-port equivalent circuit cascade model. Initially, a multi-port transient conducted EMI source model for supercapacitors is developed, taking into account the time-varying load characteristics of supercapacitors during charging and transient high-current discharge characteristics during discharging. Subsequently, a multi-port transient conducted EMI source model of the dual three-phase linear motor has been developed utilizing experimental measurement data. Leveraging the port-to-port cascade characteristics of various devices in the EML system, a dual three-phase dc-ac inverter multi-port conducted EMI model with high-frequency parasitic effects has been developed. A system-level modeling method based on the multi-port equivalent circuit cascade transient conducted EMI source modeling method is developed by cascading the multi-port equivalent circuit models of each functional component for the EML system. To evaluate the accuracy of this system-level modeling method, an experimental setup is constructed to assess transient conducted EM disturbances in a low-power EML system. The time-domain simulation results of the transient operating state are compared and analyzed with the actual operating conditions from the voltage, current, and energy perspectives, further validating the accuracy and efficacy of the EML system conducted EMI source modeling method based on a cascade of multi-port equivalent circuit models, as well as the transient conducted EM disturbances time-domain and frequency-domain characteristics.